Auditory processing disorder in patients with language-learning impairment and correlation with malformation of cortical development - Boscariol, Mirela; Guimaraes, Catarina Abraao; de Vasconcellos Hage, Simone R.; Garcia, Vera Lucia [UNESP]; Schmutzler, Katia M. R.; Cendes, Fernando; Guerreiro, Marilisa Mantovani (Elsevier B.V., 2011)
Malformations of cortical development have been described in children and families with language-learning impairment. The objective of this study was to assess the auditory processing information in children with language-learning impairment in the presence or absence of a malformation of cortical development in the auditory processing areas. We selected 32 children (19 males), aged eight to 15 years, divided into three groups: Group I comprised II children with language-learning impairment and bilateral perisylvian polymicrogyria, Group II comprised 10 children with language-learning impairment and normal MRI, and Group III comprised II normal children. Behavioral auditory tests, such as the Random Gap Detection Test and Digits Dichotic Test were performed. Statistical analysis was performed using the Kruskal-Wallis test and Mann-Whitney test, with a level of significance of 0.05. The results revealed a statistically significant difference among the groups. Our data showed abnormalities in auditory processing of children in Groups I and II when compared with the control group, with children in Group I being more affected than children in Group II. Our data showed that the presence of a cortical malformation correlates with a worse performance in some tasks of auditory processing function. (C) 2010 The Japanese Society of Child Neurology. Published by Elsevier B.V. All rights reserved.
Keywords: Auditory cortex; Perisylvian polymicrogyria; Specific language impairment; Dyslexia